Allowing the direct interaction of N-aryl α-diimines with a high valent metal chloride: one-pot WCl6-promoted formation of quinoxalinium salts. Issue 38 (21st September 2017) - Bartalucci, Niccolò; Bortoluzzi, Marco; Funaioli, Tiziana; Marchetti, Fabio; Pampaloni, Guido; Zacchini, Stefano
Abstract : BREAKING THE RULE! N -(2, 6-diisopropylphenyl) α-diimines, known to be robust ligands in coordination chemistry, convert into quinoxalinium cations by reaction with WCl6 in mild conditions. Abstract : The full potential of a high valent metal chloride as both a chlorinating and an oxidative agent was explored by allowing WCl6 to react with N -(2, 6-diisopropylphenyl) α-diimines, in CH2 Cl2 at room temperature. These α-diimines underwent unprecedented conversion to quinoxalinium cations via intramolecular C–N coupling.